Row reduced echelon Form for solving fully fuzzy system with unknown coefficients - Malkawi, Ghassan; Ahmad, Nazihah; Ibrahim, Haslinda; Alshmari, Bander (International Scientific Publications and Consulting Services, 2014)
This study proposes a new method for finding a feasible fuzzy solution in positive Fully Fuzzy Linear System (FFLS), where the coefficients are unknown.The fully fuzzy system is transferred to linear system in order to obtain the solution using row reduced echelon form, thereafter; the crisp solution is restricted in obtaining the positive fuzzy solution.The fuzzy solution of FFLS is included crisp intervals, to assign alternative values of unknown entries of fuzzy numbers.To illustrate the proposed method, numerical examples are solved, where the entries of coefficients are unknown in right or left hand side, to demonstrate the contributions in this study.